Economic and management strategies for optimizing healthcare services: A case study on telemedicine in Indonesia - Rerey, Heni Voni; Syauki, Ahmad Yanuar; Waqqosh, Abi; Limijadi, Edward Kurnia Setiawan; Ruhana, Faria (Universitas Aisyah Pringsewu, 2023)
This study explores the integration of telemedicine into the Indonesian healthcare system, focusing on the economic and management strategies that optimize service delivery. It investigates the current state of telemedicine in Indonesia, identifying key challenges and opportunities within this emerging field. The research employs a mixed-methods approach, combining quantitative data analysis with qualitative case studies, to provide a comprehensive overview of telemedicine's impact on healthcare efficiency and accessibility. The findings reveal that telemedicine offers significant potential for enhancing healthcare services in Indonesia, particularly in remote and underserved areas. However, it also highlights the need for robust economic models and effective management practices to ensure sustainable implementation. The study discusses the implications of telemedicine for healthcare policy and management, suggesting strategic approaches for its integration into the national healthcare system. It emphasizes the importance of stakeholder collaboration, infrastructure development, and policy support in realizing the full benefits of telemedicine. The research contributes to the growing body of knowledge on telemedicine in developing countries, offering valuable insights for healthcare practitioners, policymakers, and researchers. This study underscores the transformative potential of telemedicine in reshaping healthcare delivery in Indonesia, advocating for strategic investments and policy reforms to harness its full potential.